Managed the Cultural Landscape of San Blas de Ondores (Junin, Peru) - Arias Suárez, Thalia Lucero (2023)
The Salt mine of San Blas, located in the district of Ondores, province of Junin, Peru, continuously functioned as a salt extraction site from pre-Hispanic times to the 20th century. In pre-Hispanic times, production was based on the use of traditional exploitation used molds, pots and jars until the 20th century when the exploitation was industrialized, making it a place of great importance for the local mining industry. This historical trajectory is recognized and valued by the local population even though it is now abandoned. This research identified the cultural and social values that the population has of the site, being able to determine them in qualitative and quantitative terms. The results allow us to propose the management of San Blas as a cultural landscape, revaluing modern constructions, such as the Casona, as well as the existing archaeological heritage.